Chemopreventive effects of hesperidin against paclitaxel-induced hepatotoxicity and nephrotoxicity via amendment of Nrf2/HO-1 and caspase-3/Bax/Bcl-2 signaling pathways. (25th September 2022) - Gur, Cihan; Kandemir, Fatih Mehmet; Caglayan, Cuneyt; Satıcı, Emine
Abstract: Paclitaxel (PTX) is a widely used chemotherapeutic drug particularly effective against lung, breast, and ovarian cancer, though its usefulness is limited due to its multi-organ toxicity. The mechanisms underlying PTX toxicity are currently not yet known and there are no approved treatments for its control or prevention. This study aimed to investigate whether hesperidin (HSP) had a protective effect on paclitaxel-induced hepatotoxicity and nephrotoxicity from biochemical, and molecular perspectives. The rats were administered PTX 2 mg/kg, b.w. intraperitoneally for the first 5 consecutive days, then 100 or 200 mg/kg b.w. HSP orally for 10 consecutive days. Our results demonstrated that HSP decreased the PTX induced lipid peroxidation, improved the serum hepatic and renal functions (by decreasing the levels of AST, ALT, ALP, urea, and creatinine), and restored the liver and kidney antioxidant armory (SOD, CAT, GPx, and GSH). HSP also significantly reduced mRNA expression levels of NF-κB, TNF-α, IL-1β, IL-6, MAPK 14, Caspase-3, Bax, LC3A, LC3B, MMP2, and MMP9 whereas caused an increase in levels of Nrf2, HO-1, and Bcl-2 in the kidney and liver of PTX-induced rats. In addition, caspase-3, Bax, and Bcl-2 protein levels were examined by Western blot analysis, and it was determined that HSP decreased caspase-3 and Bax protein levels, but increased Bcl-2 protein levels. The findings of the study suggest that HSP has chemopreventive potential against PTX-induced hepatorenal toxicity plausibly through the attenuation of oxidative stress, inflammation, apoptosis, and autophagy. Graphical abstract: Image 1 Highlights: Hesperidin ameliorated PTX-induced hepatotoxicity and nephrotoxicity. Hesperidin suppressed inflammatory signaling pathway MAPK 14/NF-κB/TNF-α. Hesperidin regulated Caspase-3/Bax/Bcl-2 apoptotic pathway. Hesperidin suppresses PTX-induced apoptosis and autophagy. Hesperidin attenuated MMP-2 and MMP-9 levels.